Non-linear conduction due to depinning of charge order domains in Fe3O2BO3. (10th April 2017) - dos Santos, E C; da Silva, E F; Fernandes, J C; Ghivelder, L; Freitas, D C; Continentino, M A; Walmsley, L
Abstract: The oxyborate Fe3 O2 BO3 presents a charge density wave (CDW) transition close to room temperature. As we show here, this is associated with a well defined anomaly in the specific heat. Below this transition, when applying in a single crystal of Fe3 O2 BO3 a DC voltage above a temperature dependent threshold, a high current is liberated in this material. We study the conduction in single crystals of Fe3 O2 BO3 with voltage applied parallel and perpendicular to the crystallographic c axis direction. The observed currents are attributed to the depinning of charge ordered domains above a threshold voltage V T 2 that gives rise to a collective conduction due to coherent domains. Compliance limited DC data shows that above a lower threshold voltage depinning is smooth and follows a power law scaling. Similar depinning with power law scaling is also revealed in the AC conductivity.